Long-term follow-up of implantable cardioverter-defibrillators in Short QT syndrome - El-Battrawy, Ibrahim; Besler, Johanna; Ansari, Uzair; Liebe, Volker; Schimpf, Rainer; Tueluemen, Erol; Rudic, Boris; Lang, Siegfried; Odening, Katja; Cyganek, Lukas; Wolpert, Christian; Zhou, Xiao-Bo; et al. (Clinical research in cardiology, 2019)
BACKGROUND: Short QT syndrome (SQTS) is associated with sudden cardiac death and implantable cardioverter-defibrillator (ICD) implantation is recommended in this rare disease. However, only a few SQTS families have been reported in literature with limited follow-up data. - OBJECTIVES: In the recent study, we describe the outcome data of 57 SQTS patients receiving ICD implantation. This includes seven SQTS families consecutively admitted to our hospital between 2002 and 2017 as well as patients reported in published literature. - METHODS: Seven SQTS patients admitted to our hospital were followed up. Additionally, 7 studies out of a total of 626 researched articles were identified through systematic database search (PubMed, Web of Science, Cochrane Library, and Cinahl) and their data analyzed according to our model. - RESULTS: Complications during a median follow-up time of 67.4 months (IQR 6-162 months) were documented in 31 (54%) patients. Inappropriate shocks were seen in 33% due to T wave oversensing (8.7%), supraventricular tachycardia (19%), lead failure and fracture (21%). Further complications were infection (10%), battery depletion (7%) and psychological distress (3.5%). Appropriate shocks were documented in 19%. Three patients (5%) were treated with s-ICD due to recurrent complications of transvenous ICD. - CONCLUSION: ICD therapy is an effective therapy in SQTS patients. However, it is also associated with significant risk of device-related complications.